KAJIAN EKSPERIMENTAL PROBLEM BASED LEARNING PADA KETERAMPILAN BERPIKIR KRITIS MATEMATIKA SISWA SMP - Indah Sari; Arief Ertha Kusuma; Hariaty Hamid (Mathematics Education and Application Journal (META), 2025)
This study aims to determine the influence of the Problem-Based Learning (PBL) learning model on students’ mathematical critical thinking skills in grade VIII of SMPN 2 Bunyu Island. This study uses a quasi-experiment, with a sample of 63 students obtained through saturated sampling. Data on mathematical critical thinking skills were collected with five different description questions for the pretest and posttest. The research data were analyzed using descriptive statistics, an independent-samples t-test, and an N-gain score test. The descriptive analysis showed that the average score on the mathematical critical thinking tests in the experimental class using the Problem-Based Learning (PBL) model was higher than that in the control class using the conventional model. The independent-samples t-test showed t-calculate > t-table at the 5% significance level, and the follow-up test using the N-gain score showed that the average score of the experimental class was significantly higher than the average N-gain score of the control class. Thus, it was concluded that the Problem-Based Learning (PBL) learning model influenced students’ mathematical critical thinking skills in grade VIII of SMPN 2 Bunyu Island. Implementing the Problem-Based Learning (PBL) model can be an effective strategy for improving students’ critical thinking skills in mathematics.   Penelitian ini bertujuan untuk mengetahui pengaruh model Problem Based Learning (PBL) terhadap keterampilan berpikir kritis matematis siswa di kelas VIII SMPN 2 Pulau Bunyu. Penelitian ini menggunakan Quasi Eksperimen. Sampel penelitian ini berjumlah 63 siswa yang diperoleh melalui teknik sampling jenuh. Data keterampilan berpikir kritis matematis dikumpulkan dengan 5 soal uraian yang berbeda untuk pretest dan posttest. Data penelitian dianalisis dengan teknik analisis deskriptif, uji independent sample t-test dan uji N-gain score. Hasil analisis deskriptif menunjukkan skor rata-rata hasil tes keterampilan berpikir kritis matematis pada kelas eksperimen yang menerapkan model PBL lebih besar dibandingkan dengan kelas kontrol yang menerapkan model pembelajaran konvensional. Uji independent sample t-test menunjukkan nilai thitung > ttable pada taraf signifikansi  serta hasil uji lanjut menggunakan uji N-gain score diperoleh skor rata-rata N-gain kelas eksperimen lebih besar dibandingkan skor rata-rata N-gain kelas kontrol. Dengan demikian disimpulkan bahwa terdapat pengaruh model PBL terhadap keterampilan berpikir kritis matematis siswa di kelas VIII SMPN 2 Pulau Bunyu. Penerapan model PBL dapat menjadi strategi efektif untuk meningkatkan keterampilan berpikir kritis matematis siswa